M.Ö. II. VE I. BİN YILDA YUNAN VE ANADOLU HALKLARI ARASINDAKİ İLİŞKİLER - Veli ÜNSAL (Fırat University, 2019)
The Achaeans, who are the predecessors of the Hellens formed the Mycenaean (Achaean) culture in Hellas starting from the mid-2000s B.C. and brought this culture into the Aegean and the Mediterranean world. That traces of the Mycenaean culture are encountered on Western Anatolian and Mediterranean coasts indicates that the Hellens have taken this culture outside the borders of Greece. The Mycenaean ceramics found in the coastal cities of Anatolia are one of the most significant indicators of the Achaean settlement in Anatolia. With Aegean migrations around 13th century B.C., the Mycenaean culture came to an end. Many of the Hellens left their homeland and migrated to the opposite coasts of the Aegean because of these invasions. First emigrants were the Aeolians. These were followed by the Ionians. Later, Dorians settled on the southwestern coasts of Anatolia. One of the peoples who came to Anatolia during the Aegean migrations and had relations with the Hellens are the Phrygians. The Phrygians-Hellens relations were predominantly based on arts and religion. The Phrygians arts and the Hellens arts have close similarities. Religios relations, however, are known to us by the presents offered by the Phrygians kings to Delphi, one of the most significant Hellens religious centers. Another tribe which had relations with the Hellens in Anatolia is the Lydians. The relations between the Lydian Kingdom which was located right on the eastern of the Ionia and the Hellens on the Western Anatolia were not always pleasant. Almost all of the Lydians Kings launched series of attacks, when the chances arose, to dominate the Hellen City-States in Western Anatolia.